Wideband Dual-Arm Capacitively Coupled Patch Antenna for Tablet/Laptop Applications - S. Niyamanon; P. Janpangngern; C. Phongcharoenpanich (My University, 2019)
The capacitively coupled microstrip antenna for 4G and Wi-Fi applications is presented.The antenna has a compact size which can easily be installed into many types of wireless communication device.The antenna is designed on FR4 substrate with a total dimension of 70 mm × 9 mm × 0.8 mm.The structure of the antenna consists of two main parts.The T-shape feeding patch located between two radiating strips with the ground strip being placed behind them.The surface current distribution and parametric study was analyzed to determine the suitable parameters.Furthermore, the antenna prototype was fabricated and tested.The operating frequency range of the proposed antenna is between 1.7 GHz and 2.5 GHz for the |S 11 | of less than -10 dB.The antenna provides a linear polarization in a single beam direction covering approximately one quadrant of the free space with a maximum gain of higher than 1.47 dBi on the entire frequency band.
Keywords: Laptop; Wideband; Wireless Body Area Networks